Faktor-Faktor Yang Memengaruhi Pelaksanaan Good University Governance - Westim Ratang (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2022)
This study aims (1) to analyze and determine the effect of interpersonal communication on Good University Governance. (2) To analyze and determine the effect of work motivation on Good University Governance. (3) To analyze and determine interpersonal communication on Good University Governance through work motivation. The type of research used is explanatory research with a quantitative approach where the research was conducted at the University of Cenderawasih Jayapura. The variables used consist of: Interpersonal Communication (X) as the independent variable, Work Motivation (Y) as the intervening variable and Good University Governance (Z) as the dependent variable. All variables were measured using a Likert scale. The number of samples used in this study were 50 respondents who were employees of the Cenderawasih University in Jayapura. The types of data used in this study are primary and secondary data. Primary data was obtained from the results of distributing questionnaires, while secondary data was obtained from institutions related to this topic and research. Testing the instrument using the validity test and reliability test. The results showed that (1) interpersonal communication has an effect on work motivation, (2) interpersonal communication has an effect on Good University Governance, (3) work motivation has an effect on Good University Governance, and (4) interpersonal communication has an effect on Good University Governance through work motivation.